2017
DOI: 10.1186/s12889-017-4090-5
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of evidence-based messages to promote the use of physical activity to prevent and manage Alzheimer’s disease

Abstract: BackgroundThe impending public health impact of Alzheimer’s disease is tremendous. Physical activity is a promising intervention for preventing and managing Alzheimer’s disease. However, there is a lack of evidence-based public health messaging to support this position. This paper describes the application of the Appraisal of Guidelines Research and Evaluation II (AGREE-II) principles to formulate an evidence-based message to promote physical activity for the purposes of preventing and managing Alzheimer’s dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 66 publications
0
39
0
Order By: Relevance
“…Implications for policy and practice PWD are to be encouraged and facilitated to participate in appropriate forms of physical activity as part of a public health strategy and for PWD to continue to enjoy quality of life (Bowes et al, 2013;Ginis et al, 2017;Nyman & Szymczynska, 2016). Similar to a previous systematic review of qualitative studies conducted with people with physical impairments and mobility limitations (Williams, Ma, & Martin Ginis, 2017), we found that a combination of goal (goal setting (behaviour)), support (social support (unspecified)), and communication (using a credible source) strategies would be promising for promotion of physical activity among PWD.…”
Section: Limitations and Ideas For Future Researchmentioning
confidence: 99%
“…Implications for policy and practice PWD are to be encouraged and facilitated to participate in appropriate forms of physical activity as part of a public health strategy and for PWD to continue to enjoy quality of life (Bowes et al, 2013;Ginis et al, 2017;Nyman & Szymczynska, 2016). Similar to a previous systematic review of qualitative studies conducted with people with physical impairments and mobility limitations (Williams, Ma, & Martin Ginis, 2017), we found that a combination of goal (goal setting (behaviour)), support (social support (unspecified)), and communication (using a credible source) strategies would be promising for promotion of physical activity among PWD.…”
Section: Limitations and Ideas For Future Researchmentioning
confidence: 99%
“…20 Therefore, qualified Tai Chi instructors are encouraged to provide classes for PWD and their family carers so that PWD may also benefit from this exercise for their general health and wellbeing. 57,58…”
Section: Practice Implicationsmentioning
confidence: 99%
“…The Appraisal of Guidelines Research and Evaluation II (AGREE II) instrument is useful for ensuring rigor and transparency in the clinical guideline development process [13]. An adapted version of AGREE II has been used to guide the development of evidence-informed messages and resources that support delivery of PA guidelines to the general and specific populations, including Canadians with SCI [14][15][16]. This process has not yet been applied to the new SCI scientific exercise guidelines.…”
Section: Introductionmentioning
confidence: 99%